Assessing diversity among traditional Greek and foreign eggplant cultivars using molecular markers and morphometrical descriptors - Augustinos, Antonios A.; Petropoulos, Constantinos; Karasoulou, Vassiliki; Bletsos, Fotios; Papasotiropoulos, Vasilis (Spanish Journal of Agricultural Research, 2016)
Eggplant is a widely cultivated vegetable crop of great economic importance. Its long lasting history of domestication, selection and breeding has led to the development of numerous cultivars with variable traits. In the present study, we assessed the diversity levels within and among eleven Greek and foreign cultivars, using 22 morphological descriptors and two different classes of molecular markers (retrotransposon microsatellite amplified polymorphism-REMAP markers and nuclear microsatellites). Our results, in accordance with other studies in the field showed: a) the limited levels of genetic polymorphism within the cultivars; b) the high morphological and genetic divergence existing among them as indicated by the genetic distance values calculated, which could be attributed to selection, inbreeding and bottleneck effects; and c) the lack of concordance among morphological descriptors and molecular markers. Despite these, our analysis showed that the utilization of combinations of markers is an effective method for the characterization of plant material providing also useful diagnostic tools for the identification and authentication of the selected Greek cultivars.